KUALITAS PELAYANAN PADA PERTUNJUKAN DRAMATARI THE LEGEND OF RORO JONGGRANG DI RAMAYANA BALLET PRAMBANAN YOGYAKARTA - Ramadhani, Salhira; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Improving service quality will have a positive impact on the company to increase customer trust and increase customer loyalty to the company. This research aims to determine the quality of service at dance drama performances in one of the famous tourist destinations in Yogyakarta. Performed at the Ramayana Ballet Prambanan Theater and Performance Unit in Yogyakarta. This research applies a quantitative descriptive approach and uses data collection techniques such as observation, questionnaires and documentation. The results of this research are the identification of service quality that needs to be implemented: professional experience, service quality qualifications as indicated by survey results, accuracy of service delivery to visitors. Ramayana Ballet Prambanan has achieved excellent service quality as seen from direct evidence, reliability, responsiveness, empathy and guarantees provided to visitors. Keywords: Service Quality, Dance Drama, The Legend Of Roro Jonggrang.